Compact Operational Tropospheric Water Vapor and Temperature Raman Lidar with Turbulence Resolution. Issue 24 (23rd December 2019) - Lange, D.; Behrendt, A.; Wulfmeyer, V.
Abstract: We present the new Atmospheric Raman Temperature and Humidity Sounder (ARTHUS). We demonstrate that ARTHUS measurements resolve (1) the strength of the inversion layer at the planetary boundary layer top, (2) elevated lids in the free troposphere during daytime and nighttime, and (3) turbulent fluctuations in water vapor and temperature, simultaneously, also during daytime. Very stable and reliable performance was demonstrably achieved during more than 2, 500 hr of operations time experiencing a huge variety of weather conditions. ARTHUS provides temperature profiles with resolutions of 10–60 s and 7.5–100 m vertically in the lower free troposphere. During daytime, the statistical uncertainty of the water vapor mixing ratio is <2 % in the lower troposphere for resolutions of 5 min and 100 m. Temperature statistical uncertainty is <0.5 K even up to the middle troposphere. ARTHUS fulfills the stringent WMO breakthrough requirements on nowcasting and very short range forecasting. Plain Language Summary: The observation of atmospheric moisture and temperature profiles is essential for the understanding and prediction of earth system processes. These are fundamental components of the global and regional energy and water cycles; they determine the radiative transfer through the atmosphere and are critical for the cloud formation and precipitation. Also, it is expected that the assimilation of high‐quality, lower tropospheric WV and T profiles will result in a considerable improvement of the skill of weather forecast models particularly with respect to extreme events. Here we present the Atmospheric Raman Temperature and Humidity Sounder, an exceptional tool for observations in the atmospheric boundary layer during daytime and nighttime with a very short latency. This performance serves very well the next generation of very fast rapid‐update‐cycle data assimilation systems for nowcasting and short‐range weather forecasting. Ground‐based stations and networks can be set up or extended for climate monitoring, verification of weather, climate and earth system models, and data assimilation for improving weather forecasts. Key Points: Fulfills World Meteorological Organization breakthrough requirements for nowcasting/very short range forecasting in the lower troposphere Resolves strength of the inversion layer at the planetary boundary layer top and elevated lids above during daytime and nighttime Provides statistics on turbulent fluctuations in water vapor and temperature simultaneously in the lower troposphere